Minocycline is cytoprotective in human trabecular meshwork cells and optic nerve head astrocytes by increasing expression of XIAP, survivin, and Bcl-2 - Marcus Kernt; Aljoscha S Neubauer; Kirsten H Eibl; et al (Clinical Ophthalmology, 2010)
Marcus Kernt, Aljoscha S Neubauer, Kirsten H Eibl, Armin Wolf, Michael W Ulbig, Anselm Kampik, Cristoph HirneissDepartment of Ophthalmology, Ludwig-Maximilians-University, Munich, GermanyIntroduction: Primary open-angle glaucoma (POAG) is one of the leading causes of blindness. Activation of optic nerve head astrocytes (ONHA) and loss of trabecular meshwork cells (TMC) are pathognomonic for this neurodegenerative disease. Oxidative stress and elevated levels of transforming growth factor beta (TGFβ) play an important role in the pathogenesis of POAG. This study investigates the possible antiapoptotic and cytoprotective effects of minocycline on TMC and ONHA under oxidative stress and increased TGFβ levels.Methods: TMC and ONHA were treated with minocycline 1–150 μM. Possible toxic effects and IC50 were evaluated after 48 hours. Cell proliferation and viability were examined in order to assess the protective effects of minocycline on TMC and ONHA. Expression of Bcl-2, XIAP, and survivin, as well as their mRNA expression, were assessed by real time polymerase chain reaction (RT-PCR) and Western Blot analysis 48 hours after treatment with minocycline alone and additional incubation with TGFβ-2 or oxidative stress.Results: Minocycline 1–75 μM showed no toxic effects on TMC and ONHA. Under conditions of oxidative stress, both TMC and ONHA showed an increase in viability and an ability to proliferate when treated with minocycline 20–40 μM. RT-PCR and Western blotting yielded an overexpression of Bcl-2, XIAP, and survivin when TMC or ONHA were treated with minocycline 20–40 μM under conditions of oxidative stress and when additionally incubated with TGFβ-2.Conclusion: Minocycline up to 75 μM does not have toxic effects on TMC and ONHA. Treatment with minocycline 20–40 μM led to increased viability and proliferation under oxidative stress and TGFβ-2, as well as overexpression of Bcl-2, XIAP, and survivin. This protective pathway may help to prevent apoptotic cell death of TMC and ONHA and therefore be a promising approach to avoidance of progression of glaucomatous degeneration.Keywords: glaucoma, apoptosis, minocycline, trabecular meshwork, optic nerve head astrocytes